Some methods for the determination and the evaluation of non-fragmented and minimally disturbed landscape areas - Olaf Kappler (Cybergeo)
The assessment of the effect and function of non-fragmented landscape areas with minimal disturbances for vertebrata with large spatial requirements can involve some methods. The research project of the German Ministry for Education and Research which is entitled "Effects and Functions of Non-Fragmented Spaces with Minimal Disturbances for Vertebrata and Populations with Large Spatial Requirements” and led by the Country Office for Environment and Nature of Mecklenburg-Vorpommern mainly aims at looking for arguments to introduce this kind of special spaces as a protected property. Another aim consists in finding out or test methods for determination of such spaces. The more commonly-used methods of analysis and evaluation of such areas which were also used in this research project are presented in this paper, taking examples from Mecklenburg-Vorpommern, the north-eastern part of Germany.